TINDAKAN PEMERINTAH DAERAH KABUPATEN ROKAN HILIR DALAM MEMFASILITASI PENCEGAHAN NARKOBA TAHUN 2016-2017 - Galih Saputra; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The rise of drug trafficking in Rokan Hilir Regency is marked by the inclusion of Rokan Hilir Regency in the red zone of the danger of drugs, p stipulated by the National Narcotics Agency based on visible cases and local people who do not understand drug use against drugs, economic crush is also a factor to get a bigger income. In addition, it is easy to access drug entry through rat ports. The Rokan Hilir District BNK records that drug trafficking in Rokan Hilir is very worrying, because it not only targets the general public but also extends widely to children and school students, so Rokan Hilir Regency is currently classified as a drug emergency area. The purpose of this study was to determine the actions of the government of Rokan Hilir Regency in drug prevention and to know the inhibiting factors of the Rokan Hilir District Government in the prevention of drugs. The theory used in this study is the theory of Government Action. The research method used is a qualitative research method using descriptive methods. Based on the results of this study, 1) Rokan Hilir Regency does not yet have a regional regulation on drugs, 2) establishes BNK to carry out prevention in drug trafficking, 3) the government has not made a circular about drugs to ASN, but references to the dangers of drugs are included in the regulations Regent No. 21 of 2015 concerning the discipline of ASN employees, 4) there is no written planning through assignment letters, but the instruction is carried out informally such as the socialization of the dangers of drugs, 5) all forms of licensing including prevention of drug trafficking are made by DPMPTSP through delegation of authority from the Regent. Keywords: Government Actions, Drugs